Achieving Success As a 21st Century Manager. - Frost, Dean E. (Studien Zum Physik- und Chemielernen Series, 2021)
This book is about taking personal control of your management career by planning for your development outside of training sessions or university degree programs. Careers and organizations are changing rapidly so personalizing your own training and competency development is critical. Included in this book are self-evaluations for cognitive competence, virtual competence, emotional competence, cross-cultural competence, socialization competence, health competence, and competencies in spotting leadership differences and situational recognition.